Strategi Pusat Pembelajaran Keluarga (Puspaga) Dalam Menurunkan Angka Perceraian Di Kelurahan Putat Jaya Surabaya - Ramadhani, Fiska Devina; Rusliansyah, Aliatun Nisa; Firdausi, Firdausi; Reviandani, Oktarizka (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study aims to analyze the strategy of the Family Learning Center (PUSPAGA) in reducing divorce rates in Putat Jaya Village, Surabaya. The high divorce rate in the area has encouraged the need for preventive efforts through strengthening family resilience. This research employed a qualitative method with a case study approach. Data collection techniques included interviews, observations, and documentation involving PUSPAGA administrators, counselors, village officials, and community members as service beneficiaries. The analysis used Fred R. David’s strategic management theory, which consists of strategy formulation, strategy implementation, and strategy evaluation. The results show that PUSPAGA implements its strategies through premarital classes, parenting programs, family counseling, community education, and the utilization of digital media and SIAPPPAK services. The strategies were implemented directly through activities at community halls and online to expand public access to services. Strategy evaluation was conducted through activity monitoring and community feedback regarding the provided services. The existence of PUSPAGA has contributed to improving public understanding of family resilience, household communication, and preventive family conflict resolution. However, the program implementation still faces challenges, including low community participation and limited resources in optimizing services. This study is expected to serve as a reference for local governments in strengthening family service strategies to reduce divorce rates. Keyword : PUSPAGA; strategy; divorce; family resilience; public service